JRuby Rails Web Application Development - Vohra, Deepak (Springer eBooks, 2014)
This SpringerBrief explains how to create a Rails web application with JRuby, a 100% Java implementation for Ruby. This brief demonstrates how Oracle® WebLogic servers and JBoss® application servers deploy the JRuby application, how JRuby runs on the Java® Virtual Machine, and how JRuby is the basis for popular websites including LinkedIn, Oracle Mix, and Mingle. The Oracle® database and Oracle® MySQL database are used as the basis for the JRuby Rails application. Chapters also cover enabling Flash, developing the JRuby application using Ruby syntax, and deploying applications through Java EE WAR. Hands-on and practical, this SpringerBrief is designed for web developers and researchers interested in JRuby. It is also a useful guide for advanced-level students interested in creating a new web application.